Isolation of Campylobacter Species in the Stool of Under Five Children With Acute Diarrhoea in a Tertiary Care Hospital of Bangladesh - Dey, Suborna; Das, Rajib; Haque, Md Moynul; Das, Premananda; Das, Shantanu; Habib, Farjana Binte; Rahman Chowdhury, Sultana Mehnaz; Rahman, Mohammed Mirazur; Aman, Sakib; Hasan, Md Nazmul (Bangladesh Medical Journal, 2021)
Campylobacter species is the main etiology of gastroenteritis due to bacteria. To determine prevalence of Campylobacter species in stool of children less than five years of age with acute diarrhoea, this observational study was conducted in the Department of Microbiology, Sylhet M A G Osmani Medical College, Sylhet from January to December, 2017. Stool samples were collected from 162 under-five children with acute diarrhoea admitted in the Department of Paediatrics. Isolation of Campylobacter species were done by stool culture. About two third of the children were male (65.4%) and more than one fourth of the affected children (26.65%) were in age group 6-12 months. Campylobacter species was isolated in 24 (15%) sample and among them, Campylobacter jejuni were 22 (91.7%) and Campylobacter coli were 2 (8.3%). Isolation rate of Campylobacter species did not differ significantly between age group of 6-12 months and above 12 months (p=0.211) of age; male and female children (p=0.288); among socioeconomic status (p=0.673) and between residential status (p=0.108). Isolation rate of Campylobacter species are frequent among under five children with acute diarrhea and most of the children came from low socioeconomic background and were male. However, a large multicenter study needs to be conducted to generate more evidence regarding the issue. Bangladesh Med J. 2020 Sept; 49(3) : 11-16